A tetrad cognitive presentation of Gerstmann syndrome : a rare manifestation of stroke - Siti Nur Izni SMA; Kevin WCS; Ahmad Khaldun Ismail (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Gerstmann Syndrome is a rare neurological presentation due to a lesion in the left dominant parietal lobe, manifesting as a tetrad of agraphia, acalculia, finger agnosia and right-left disorientation. We present a case of a 52-year-old man, right handdominant, who presented to the Emergency Department with acute confusion for one day. He was disorientated to time, place and person. Focused neurological examination revealed atypical signs of acute stroke, comprising agraphia, acalculia, finger agnosia and right-left disorientation. Stroke protocol was activated and he underwent computed tomography brain perfusion, which confirmed a large penumbra area at the left middle cerebral artery territory. Computed tomography angiogram of the carotid arteries showed a long segment thrombosis in the left internal carotid artery. Emergency thrombectomy was abandoned due to impenetrable hard thrombus. He was treated with dual antiplatelet therapy and discharged after three days with partial improvement in terms of following commands, simple calculations and reduced finger agnosia. He was scheduled for outpatient follow up. This case highlights Gerstmann syndrome as an atypical manifestation of acute stroke.